The analysis of running distances in national teams in 2010 and 2014 FIFA World Cup and estimation of oxygen consumption capacity based on these distances - Marangoz, I. (Journal of Education and Training Studies, 2018)
This study aims to analyze running distances in national teams during 2010 and 2014 FIFA World Cup and to propose a new program which estimates oxygen consumption capacity based on running distances. The data were evaluated by SPSS 22.0 statistical package program. The findings demonstrate that among teams participating in 2010 and 2014 FIFA World Cup, the lowest average running distance and estimated VO2max values belong to Brazil with 7398.77 meters and 43.84 ml/kg/m, respectively. On the other hand, the highest average running distance and estimated VO2max values belong to Australia with 10598 meters and 67.69 ml/kg/m, respectively. The average running distance and estimated VO2max value in national teams participating in 2010 FIFA World Cup was 9635.54 meters and 60.52 ml/kg/m, while they were 9095.82 meters and 52 ml/kg/m in 2014 FIFA World Cup, respectively.